Grave importance - Shaw, Vivian (A Dr. Greta Helsing novel, 2019)
"A charmingly witty fantasy adventure in the world of Strange Practice, starring Dr. Greta Helsing, doctor to the undead, who must solve a dangerous medical mystery at a secret French spa for mummies. Oasis Natrun: a private, exclusive, highly secret luxury health spa for mummies, high in the hills above Marseille, equipped with the very latest in therapeutic innovations both magical and medical. To Dr. Greta Helsing, London's de facto mummy specialist, it sounds like paradise. But when Greta is invited to spend four months there as the interim clinical director, it isn't long before she finds herself faced with a medical mystery that will take all her diagnostic skill to solve. A peculiar complaint is spreading among her mummy patients, one she's never seen before. With help from her friends and colleagues -- including Dr. Faust (yes, that Dr. Faust), remedial psychopomps, a sleepy scribe-god, witches, demons, a British Museum curator, and the inimitable vampyre Sir Francis Varney -- Greta must put a stop to this mysterious illness before anybody else crumbles to irreparable dust... ...and before the fabric of reality itself can undergo any more structural damage."--